The Representation of False Prophets in Polemical Discourses: A Comparative Analysis - Spampinato, Gaetano (ARYS. Antigüedad: Religiones y Sociedades, 2023)
In this article, I analyse some “transversal” polemical motifs (adopted by both “pagans” and Christians) in the representation of Alexander of Abonouteichos, offered in the homonymous work by Lucian of Samosata, and in the description of the Montanists in heresiological sources, focusing in particular on the polemists who are quoted by Eusebius of Caesarea. This analysis attempts to highlight how, despite the differences between the mentioned authors, it is possible to find some common points in the representation of the “false prophets” that is often due to the same literary references. In particular, I analyse the way of presenting the life and behaviour of these characters and their way of delivering prophetic messages.